Effects of Non-Spatial EU Policies on Spatial Developments - the Case of the Netherlands - David Evers (European Regional Science Association (ERSA), 2005)
Although the European Union has had no formal power to conduct spatial planning as such, many of its policies have had a clear impact on urban and regional development in the member states. Examples include the encouragement of certain kinds of development in particular regions via the structural funds or the designation of Trans- European Networks and the discouragement of development as a result of Natura2000 zones, air and water quality standards. At the same time, EU agricultural policy has left a clear mark on European rural areas. In addition, competition policy (particularly state aid caps and rules on public procurement) can have an impact on planning processes, while the enlargement of the common market will affect regional economic development. This paper will draw on experiences in the Netherlands regarding the cumulative effects of EU sectoral policies and make some suggestions on how the concept of territorial cohesion, included in the Constitution, may provide a vehicle for reconciling potential policy conflicts.
Keywords: 330